A pioneering FreeSurfer volumetric study of a series of patients with mesial temporal lobe epilepsy and hippocampal sclerosis with comorbid depression. (30th May 2021) - de Figueiredo, Nathália Stela Visoná; Gaça, Larissa Botelho; Assunção-Leme, Idaiane Batista; Mazetto, Lenon; Garcia, Maria Teresa Fernandes Castilho; Sandim, Gabriel Barbosa; Alonso, Neide Barreira; Centeno, Ricardo Silva; Filho, Gerardo Maria de Araújo; Jackowski, Andrea Parolin; Júnior, Henrique Carrete; Yacubian, Elza Márcia Targas
Highlights: A pioneering Freesurfer study analysed MRIs of patients with MTLE-HS and depression. MTLE-HS patients had smaller hippocampi than controls, replicating ENIGMA study. Depression group had similar MRI pattern regardless of age, sex and brain volume. No differences in cortical regions of interest occurred in patients with depression. The severity of depression not explain the negative results found in this series. Abstract: Depression is the most frequent psychiatric comorbidity in patients with mesial temporal lobe epilepsy (MTLE) and hippocampal sclerosis (HS). This study aimed to confirm whether patients with comorbid depression have different volumetric patterns on magnetic resonance imaging, analysing the influence of HS sides. Psychiatrists conducted semi-structured interviews with 75 patients, who were divided into non-depression group (NDG, n = 52) and depression group (DG, n = 23), and compared with 98 controls. The FreeSurfer software was used in the volumetric analysis of the estimated total intracranial volume (eTIV), bilateral cortical and subcortical regions of interest (ROIs), and for presence of left (L-, n = 41) or right (R-, n = 34) MTLE-HS. Twenty-three (30.7%) patients had depression, of whom 14 (34.1%) had l -MTLE-HS and 9 (26.5%) had R-MTLE-HS. No difference was observed between DG and NDG vs. controls in terms of eTIV and cortical ROIs, regardless of the severity of depression. In patients with l -MTLE-HS, the eTIV in the DG was reduced in comparison with that in the NDG and control group, with a small effect size. Hippocampal reduction occurred ipsilateral to HS in the l -MTLE-HS and R-MTLE-HS subgroups when DG and NDG were compared with controls, as expected according to Enhancing Neuro Imaging Genetics through Meta-Analysis (2018).